#TITLE_ALTERNATIVE# - (NIM 12403001), RUBEN
Principally Indonesia is a terrain with relatively high seismic activity. By the chains of disaster caused by the earthquakes, so the study and evaluation about earthquake hazard is needed. One of the methods to analyze theearthquake risk probability is to begin with doing a seismic hazard study. The study of seismic hazard can be applied in two methods, deterministic method and probabilistic method. In this case, analysis and evaluation with probabilistic approximation (PSHA) will be practiced. This study is meant to analyse the ground movement parameter and peak ground acceleration, according to geological condition and history of seismicity in Indonesia especially Sumatera. This study is practiced by using probabilistic seismic hazard analysis (PSHA) method, where all potensial earthquake source that affects the seismicity in Sumatera is considered. Based at the potensial earthquake sources and recent earthquake records, model of earthquake source zone of Sumatera can be depicted.